Adverse drug reactions due to opioid analgesic use in New South Wales, Australia: a spatial-temporal analysis - Wei Du; Shanley Chong; Andrew J. McLachlan; Lan Luo; Nicholas Glasgow; Danijela Gnjidic (BMC, 2019)
Abstract Background Pharmaceutical opioid analgesic use continues to rise and is associated with potentially preventable harm including hospitalisation for adverse drug reactions (ADRs). Spatial detection of opioid-related ADRs can inform future intervention strategies. We aimed to investigate the geographical disparity in hospitalised ADRs related to opioid analgesic use, and to evaluate the difference in patient characteristics between areas inside and outside the geographic clusters. Methods We used the all-inclusive Admitted Patient Dataset for an Australian state (New South Wales, NSW) to identify patients admitted for opioid-related ADRs over a 10-year period (July 2004 to June 2014). A space-time analysis was conducted using Kulldroff's scan statistics to identify statistically significant spatial clusters over time. Relative risk (RR) was computed with p-value based on Monte Carlo Simulation. Chi-square test was used to compare proportional difference in patient clustering. Results During the study period, we identified four statistically significant geographic clusters (RRs: 1.63-2.17) during 2004-08; and seven clusters (RRs: 1.23-1.69) during the period 2009-14. While identified high-risk clusters primarily covered areas with easier access to health services, those associated with socioeconomically disadvantaged areas and individuals with mental health disorders experienced more unmet healthcare needs for opioid analgesic safety than those from the rest of the State. Older people (≥65 years and over) accounted for 62.7% of the total study population and were more susceptible to opioid-related ADRs than younger people,. In the first five-year period the clusters included a greater proportion of people with cancer in contrast to the second five-year period in which there was a lesser proportion of people with cancer. Conclusions These results suggest that there is significant spatial-temporal variation in opioid-related ADRs and future interventions should target vulnerable populations and high-risk geographical areas to improve safer use of pharmaceutical opioid analgesics.